Christ-Siemens-Touraine Syndrome: A Case Report and Review of the Literature - Sepideh Mokhtari; Saeedeh Mokhtari; Ali Lotfi (Case Reports in Dentistry)
Ectodermal dysplasia is a rare disorder with defects in two or more of the following structures: the teeth and the skin and its appendages including hair, nails, eccrine, and sebaceous glands. Anhidrotic ectodermal dysplasia is the most common type of disease. This rare disorder, also known as Christ-Siemens-Touraine syndrome, manifests as a triad of hypotrichosis, asteatosis, and anhidrosis. In view of the rarity of this entity, a classical case of anhidrotic ectodermal dysplasia is reported. We have also provided a review of recent investigations in the area of dental abnormalities in this syndrome.